Effectiveness of Interpersonal Psychotherapy-Trauma For Depressed Women with Childhood Abuse Histories - Duberstein, Paul R. (J Consult Clin Psychol, 2018)
BACKGROUND: Women with depression and childhood sexual abuse histories constitute more than 20% of the female patient population in publicly-funded community mental health centers (CMHCs). Interventions are needed that address depression and post-traumatic stress disorder (PTSD) symptoms and social health. METHOD: We compared Interpersonal Psychotherapy-Trauma (IPT-T), an IPT adaptation for this population and setting, to Clinic Psychotherapy (CP). CP clinicians were free to implement the psychotherapy of choice. Women (n=162; 54% White, 10.5% Hispanic; 52.2% Medicaid-insured) with a major depressive episode (MDE) and history of sexual abuse before 18 were randomly assigned to IPT-T or CP. Participants were offered 16 free sessions of IPT-T or CP. Outcomes were MDE remission, improved depression (Beck Depression Inventory, Hamilton Depression Rating Scale) and PTSD symptoms (Modified PTSD Symptom Scale), and improved social health (e.g., UCLA Loneliness Scale). Weighted generalized estimating equations were used to examine outcomes at eight (primary) and 20 (secondary) months post-randomization. RESULTS: IPT-T led to greater improvements in PTSD symptoms and many social health indicators, including loneliness and social support, at both eight- and 20-month follow-up. Effect sizes ranged from .18 to .39 at the primary endpoint (eight months). IPT-T and CP yielded comparable improvements in depression symptoms and MDE remission. CONCLUSION: Evidence-based psychotherapies like IPT-T are needed in CMHCs, where some of the most vulnerable patients receive treatment. With comparable findings for depression, IPT-T’s superior improvements in social health and PTSD symptoms are cause for optimism. IPT-T should be evaluated in dissemination trials.